New process control strategy for wastewater chlorination and dechlorination using ORP/pH - Kim, H (Water science and technology : a journal of the International Association on Water Pollution Research, 2006)
Due to its efficiency and relatively low capital demanding, many wastewater treatment plants have applied chlorination for disinfection of treated wastewater before discharging it. However, determination of optimal doses of chlorine for chlorination and sulfite for dechlorination, which removes residual chlorine, should made to guarantee complete destruction of microorganisms in treated wastewater and to protect aquatic life in a receiving stream. In this study, a new ORP/pH based approach to determine endpoints of breakpoint chlorination and of dechlorinating titration and to optimize doses of chlorine and sulfite. In this new method, significant points on the ORP and pH profiles occurring during the titrations for chlorination and dechlorination were utilized to determine chlorine demand and sulfite dosage